Digital Video Acquisition and Optimization Techniques for Effective Animal Tracking in Behavioral Ecotoxicology. (6th September 2022) - Henry, Jason; Bai, Yutao; Wlodkowic, Donald
Abstract: Behavioral phenotypic analysis is an emerging and increasingly important toolbox in aquatic ecotoxicology. In this regard digital video recording has recently become a standard in obtaining behavioral data. Subsequent analysis requires applications of specialized software for detecting and reconstructing animal locomotory trajectories as well as extracting quantitative biometric endpoints associated with specific behavioral traits. Despite some profound advantages for behavioral ecotoxicology, there is a notable lack of standardization of procedures and guidelines that would aid in consistently acquiring high‐quality digital videos. The latter are fundamental for using animal tracking software successfully and to avoid issues such as identification switching, incorrect interpolation, and low tracking visibility. Achieving an optimized tracking not only saves user time and effort to analyze the results but also provides high‐fidelity data with minimal artifacts. In the present study we, for the first time, provide an easily accessible guide on how to set up and optimize digital video acquisition while minimizing pitfalls in obtaining the highest‐quality data for subsequent animal tracking. We also discuss straightforward digital video postprocessing techniques that can be employed to further enhance tracking consistency or improve the videos that were acquired in otherwise suboptimal settings. The present study provides an essential guidebook for any aquatic ecotoxicology studies that utilize digital video acquisition systems for evaluation of behavioral endpoints. Environ Toxicol Chem 2022;41:2342–2352. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.